Safety, strength and simplicity of efavirenz in pregnancy - Prinitha Pillay; Vivian Black (AOSIS, 2012)
The WHO recommends starting lifelong ART for all pregnant women with a CD4 count at or below 350 cells/mm³, which recognises the important component of 'when to start' and the role that timing of initiation plays in reducing mortality and disease progression. The data on 'what to start' are conflicting, and options for resource-limited settings are limited. The choice of an ART regimen for pregnant women is complicated by the need to take into account the health and safety of both the mother and baby. Particularly contentious is whether to use a nevirapine- (NVP) or efavirenz- (EFV) based regimen. This review presents the latest evidence on the safety and efficacy of EFV and NVP in pregnancy and offers recommendations for improving maternal and child health outcomes and avoid mother-to-child transmission as South Africa moves toward turning back the tide on its HIV epidemic.